Antigen down format photoelectrochemical analysis supported by fullerene functionalized Sn3O4. Issue 54 (4th June 2020) - Xu, Rui; Du, Yu; Leng, Dongquan; Liu, Lei; Li, Yuyang; Ren, Xiang; Fan, Dawei; Wang, Huan; Wei, Qin
Abstract : Herein, a smart competitive-type photoelectrochemical (PEC) sensor based on an antigen-down (Ag-down) format for procalcitonin (PCT) detection is proposed. Abstract : Herein, a smart competitive-type photoelectrochemical (PEC) sensor based on an antigen-down (Ag-down) format for procalcitonin (PCT) detection is proposed. A fullerene sensitized flower-like Sn3 O4 nano-structure is used as the photoactive platform, and FeS2 is labeled on the secondary antibody as a signal adjusting element. The sensor exhibits excellent sensitivity and great stability.